(untitled) (American Journal of Islam and Society, 1995)
Organizations are an indispensable part of our lives, for they provide services for satisfying our basic needs. Central to any organization’s performance is the motivation of its members. Indeed, organizational motivation is related closely to some fundamental questions in organization theory in particular and to public administration in general. Such questions focus on how organizations can be made efficient and responsive or accountable to their clients. Since organizations are simply human collectivities, in essence these questions apply to organizational members and, in particular, to what motivates them to be efficient and responsive. Although various models of organization have addressed, either implicitly or explicitly, the question of motivation in organizations, they have yet to come up with satisfactory answers. The significance of organizational motivation does not consist of its close relationship to the fundamental questions of organizational efficiency and responsiveness alone, but also of its relevance to how organizations are structured. As this latter consideration may affect such concepts as human dignity, freedom, respect, brotherhood, and justice, this is tantamount to saying that organizational structures are not morally or spiritually neutral, inasmuch as these values have moral and spiritual roots. Organizational structures are founded on certain underlying assumptions about human nature and motivation that underpin several principal organization models. One common characteristic of these models is the assumption that the individual has certain self-centered needs that govern his/her behavior and that the organization can, by satisfying these needs, motivate the individual to contribute towards the ...